2019
DOI: 10.1111/vco.12529
|View full text |Cite
|
Sign up to set email alerts
|

Immune dysregulation and osteosarcoma: Staphylococcus aureus downregulates TGF‐β and heightens the inflammatory signature in human and canine macrophages suppressed by osteosarcoma

Abstract: Since William Coley utilized bacterial immunotherapy to treat sarcomas in the late 19th century, an association between infection and improved survival has been reported for human and canine osteosarcoma patients. One of the reasons for this improved survival is likely a reactivation of the host immune system towards an inflammatory anti‐tumour response, and one of the key players is the macrophage. Yet, despite their importance, the response of macrophages to infectious agents in the context of osteosarcoma h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Moreover, the depletion of macrophages reversed these anti-tumor responses ( 62 ). Besides, infection upregulates the cytokine secretion of inflammatory macrophages, including tumor necrosis factor-α (TNF-α) and interferon- γ (IFN- γ ), and reactivate the immune system towards anti-tumor response to attenuate immunosuppression induced by osteosarcoma ( 63 ). Although these models cannot precisely mimic the local inflammatory microenvironment of osteosarcoma, these preclinical researches, together with the above clinical data, provide a new understanding of the role of macrophages and the inflammatory response in osteosarcoma.…”
Section: Macrophages and Osteosarcomamentioning
confidence: 99%
“…Moreover, the depletion of macrophages reversed these anti-tumor responses ( 62 ). Besides, infection upregulates the cytokine secretion of inflammatory macrophages, including tumor necrosis factor-α (TNF-α) and interferon- γ (IFN- γ ), and reactivate the immune system towards anti-tumor response to attenuate immunosuppression induced by osteosarcoma ( 63 ). Although these models cannot precisely mimic the local inflammatory microenvironment of osteosarcoma, these preclinical researches, together with the above clinical data, provide a new understanding of the role of macrophages and the inflammatory response in osteosarcoma.…”
Section: Macrophages and Osteosarcomamentioning
confidence: 99%
“…However, they have not yet been used in clinical practice because of unavoidable limitations, such as overfitting due to small samples 12 . In recent decades, increasing evidence has indicated that the immune response is actively involved in OS occurrence and progression 13 . Immune genes act as pivotal regulator of immune response 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…They maintain the body's self-tolerance by strictly regulating the immune function and reducing the damage inflicted on the surrounding tissues 16 . However, OS cell may use these immune genes to escape the immune system and achieve a favorable environment for their growth 13 , 17 . Given the critical role of immune molecules in OS prognosis, these immune-related genes (IRGs) deserve further study.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, it appeared that IL33 signaling could be associated with the immune response to tumorigenesis. Interestingly, impairment of antitumor immune response has been previously described for patients with OS [29]. Since the functional role of IL33 in the osteosarcomagenesis remains obscure, more experiments are warranted to unveil the underlying mechanism in the future study.…”
Section: Discussionmentioning
confidence: 92%